Class, Culture and Space - Horstmann, Alexander (2002)
In the present social and cultural transformation of South Thailands cultural politics, ideologies involving the family, gender and home provide the cultural codes in social dramas of the state, the media and social and religious movements. This study looks at micropolitics and the nesting of the political action of everyday life in larger, ultimately global structures of power. Exploring the making of class, culture and space, the production and consumption of culture is understood as work which involves the constant negotiation of boundaries